NATIONAL OCCUPATIONAL SAFETY AND HEALTH POLICIES - Jovevski, Lazar (Harmonius - Journal of Legal and Social in Studies in South East Europe, 2021)
This paper provides a scientific overview of how to create effective and applicable policies for creating a system of safe and healthy workplaces. The author deals with general settings for creating labor policies in the field of occupational safety and health, while explaining the “soft” and “hard” elements of occupational safety and health policies. The paper analyses the instruments of occupational safety policies from which stem normative acts as a basic instrument, and from the so-called “soft” instruments in labour, special attention is paid to strategies and goals for effective occupational safety and health policies, and dignified jobs. The author also studies international policies and normative standards for OSH, as well as steps leading to improper policies for protection at work. In this paper, concrete proposals and solutions are given through an analysis of what safety and health policy should be and how they should be implemented in the Macedonian system of protection at work.
Keywords: Occupational. – Health. – Safety. – Policies. – Labour. – Norm